Pengelolaan Pembiyaan Pendidikan Dalam Meningkatkan Sarana Dan Prasaran Dimadrasah Aliyah Daarussalam Pematang Duku Timur Bengkalis. - Siti Khodijah; Nur adila zulfa (Universitas Palangka Raya, 2023)
Abstract The purpose of this study is to determine the management of educational financing in improving facilities and infrastructure at Madrasah Aliyah Darussalam Pematang Duku Age, determining strategies using case studies, this research is a qualitative research that focuses on managing educational financing in improving facilities and infrastructure at Madrasah Aliyah Darussalam The source of this data comes from the school principal, treasurer, deputy head of facilities and infrastructure, committees and technical foundations. Data collection using interviews and documentation of data analysis includes data collection, data reduction, data display and drawing conclusions. The results of his research are management of education funding in improving facilities and infrastructure. in the madrasah aliyah daarussalam through three prisoners, namely a) the planning stage. The planning process for education financing in madrasah aliyah daarussalam is good, this is evidenced by holding deliberations in planning education financing once a year and involving all elements of the school, namely the head of the madrasa, data operators, treasurer of the madrasa, representatives of the field madrasah committee and teachers b) Implementation The implementation of financing at the Daarussalam Aliyah Madrasah was not optimal, the implementation was carried out in accordance with the planning that was discussed, but in its implementation there were several sudden needs. so that inevitably the school will reduce or even cut the budget for facilities and infrastructure.